ANALISIS KEBUTUHAN PENGEMBANGAN LEMBAR KERJA MURID BERBASIS MODEL PROBLEM BASED LEARNING TERINTEGRASI SDGs PADA MATERI EKOSISTEM - Afani, Fadilla; Helendra; Darussyamsu, Rahmawati; Kurniati, Rahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the needs for developing student worksheets (LKM) based on the Problem Based Learning (PBL) model integrated with the Sustainable Development Goals (SDGs) on ecosystem material for Phase E senior high school students. This study used a qualitative descriptive method oriented towards product development, with a biology teacher and 35 Phase E students at SMAN 6 Padang as subjects. Data were collected through interview guidelines and questionnaires, then analyzed using Miles and Huberman's Interactive Analysis, covering data reduction, data display, and conclusion drawing. The results showed that although the Independent Curriculum (Kurikulum Merdeka) had been implemented, the teacher had not developed a PBL-based worksheet, and the application of SDGs in learning was still not optimal. Students considered ecosystem material the most difficult to understand due to numerous confusing terms and its memorization-oriented nature. Students showed strong interest in using worksheets integrated with real environmental issues and SDGs. Based on these findings, the development of an SDGs-integrated, PBL-based student worksheet on ecosystem material is needed to support meaningful and contextual biology learning.